Immune responses against domain I of β(2)-glycoprotein I are driven by conformational changes: domain I of β(2)-glycoprotein I harbors a cryptic immunogenic epitope - de Laat, Bas; van Berkel, Miranda; Urbanus, Rolf T; Siregar, Berdien; de Groot, Philip G; Gebbink, Martijn F; Maas, Coen (John Wiley & Sons Inc., 2011)
OBJECTIVE: The presence of autoantibodies against a cryptic epitope in domain I of β(2)-glycoprotein I (β(2)GPI) is strongly associated with thrombotic events in patients with the antiphospholipid syndrome. We hypothesized that a conformational change could be a trigger for the formation of antibodies against domain I of β(2)GPI. Therefore, we investigated whether immune responses against β(2)GPI are related to its conformation. METHODS: Conformational changes in β(2)GPI were studied using various techniques, either upon binding to cardiolipin or after disruption of the internal disulfide bonds. The immunogenicity of β(2)GPI in different conformations as well as the individual domains of β(2)GPI were studied in vivo by monitoring the generation of antibodies after intravenous administration of β(2)GPI to mice. Furthermore, plasma samples from these mice were assessed for lupus anticoagulant activity and thrombin-antithrombin complex levels. RESULTS: We observed that the interaction of β(2)GPI with cardiolipin induced a conformational change in β(2)GPI: electron microscopy revealed that β(2)GPI assembled into polymeric meshworks. We next investigated the immunogenicity of both human and murine β(2)GPI in mice. Both human and murine β(2)GPI combined with cardiolipin and misfolded β(2)GPI triggered antibody formation against the native protein as well as against domain I of β(2)GPI, while native β(2)GPI was not immunogenic. In addition, we observed that anti-domain I antibodies developed in mice injected with domain I of β(2)GPI, and that antibodies did not develop in mice injected with domains II-V. The induced anti-domain I antibodies prolonged the dilute Russell's viper venom plasma clotting time. The plasma of mice with anti-domain I antibodies had increased levels of circulating thrombin-antithrombin complexes. CONCLUSION: The results of our studies indicate that the exposure of cryptic epitopes due to conformational changes in β(2)GPI can induce autoantibody formation.
Keywords: Animals; Antiphospholipid Syndrome/immunology; Autoantibodies/immunology; Cardiolipins/metabolism; Epitopes/genetics; Immunity, Innate/physiology; Immunogenetic Phenomena/genetics; Mice; Mice, Inbred BALB C; Models, Animal; Protein Binding; Protein Conformation; beta 2-Glycoprotein I/chemistry; Journal Article; Research Support, Non-U.S. Gov't